Digital Payment Revolution: Reshaping Student Transactions at ISB Atma Luhur - Seno Hadi; Krisna Adiyarta; Devi Irawan; Arifin , Arifin (Jurnal Multidisiplin Indonesia, 2025)
This study investigates the factors influencing digital wallet adoption among ISB Atma Luhur Pangkalpinang students through a modified UTAUT model, addressing the growing need for digital payment solutions in higher education. The research uniquely integrates hedonic motivation, habit, and promotion factors into the UTAUT framework, extending our understanding of digital wallet adoption in campus environments.The study employed a quantitative approach, collecting data from 300 students through purposive sampling and analyzing it using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings revealed that performance expectancy emerged as the strongest predictor of behavioral intention (β=0.794), followed by effort expectancy (β=0.585) and hedonic motivation (β=0.353), aligning with Yang et al.'s (2021) observations on digital payment adoption patterns. Behavioral intention demonstrated a robust mediating effect on use behavior (β=0.804), supported by promotion (β=0.581), while social influence and habit showed no significant impact. The research model exhibited strong predictive capability, explaining 87.5% of variance in behavioral intention (R²=0.875) and 75.2% in use behavior (R²=0.752). These findings provide crucial theoretical and managerial implications for developing effective digital wallet adoption strategies in higher education institutions, particularly focusing on enhancing user experience and perceived benefits.